Understanding Level of Technology Pedagogy and Content Knowledge (TPACK) Students of Architectural Engineering Education Study Program - Busono, Rr. Tjahyani; Mardiana, Riskha; Dwidayati, Kunthi Herma (Universitas Pendidikan Indonesia, 2021)
Â The Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers states that a teacher must have four competencies, namely pedagogical competence, personality, social and professional competences. A teacher is expected to pay attention to the material, strategy, technology or surrounding culture in helping to realize active, creative, fun and meaningful learning. One of the uses of ICT in education is needed as an effort to improve the efficiency and effectiveness of the learning process. However, there are many obstacles faced in its application, including a lack of teacher understanding of technology. Technological Pedagogical And Content Knowledge (TPACK) is a framework that describes the knowledge needed by teachers to integrate technology in designing, implementing and evaluating learning. This study aims to determine the level of understanding of the Technological Pedagogical and Content Knowledge of students of the Architectural Engineering Education Study Program who are also prospective teachers. The research method used is descriptive evaluative with a quantitative approach. Retrieval of data using a survey method of 35 respondents from students of the Architectural Engineering Education Study Program who have been and are currently participating in the Field Experience Program at Vocational High Schools in various regions in West Java. The instrument used was a closed questionnaire where each statement was based on each TPACK component. The results showed that the average level of understanding of Architectural Engineering students towards TPACK was in the good category. The highest value is in the aspect of Technology Knowledge (TK), which is knowledge about technology with a very high category.